Sejarah Sanggar Wayang Sasono Budoyo Kecamatan Ambulu Kabupaten Jember Tahun 1995-2013 - Kristina Dwi Andriana (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Sanggar Sasono Budoyo is a puppet art studio located in Sumberan Village, Ambulu District, Jember Regency. This study aims to determine the background of the establishment of Sanggar Sasono Budoyo, the development of the studio from 1995 to 2013, and efforts to preserve puppetry at Sanggar Sasono Budoyo. This study uses a historical research method with four stages: heuristics, criticism, interpretation, and historiography. The data collection techniques in this study use interviews, observations, and relevant literature reviews to answer the research questions. The results show that Sanggar Sasono Budoyo was established in 1995 primarily to create a formal and organized art forum. In addition, the establishment of the studio also facilitated the acceptance of students interested in learning puppetry because learning activities could be carried out in a more structured and focused manner through good and official studio management. The purpose of establishing this studio was to contribute to the intellectual development of the nation. Through puppetry and culture, it was hoped that the younger generation could learn about manners, how to serve the community and the country, and become individuals with noble character. In 2000, Sanggar Sasono Budoyo not only functioned as a place of entertainment, but also as a training center for puppeteers for the general public.
Validasi file repositori 11 Juni 2026_Magang SP (Aurora)_Firli
Keywords: Art Studio; History; Shadow Puppet; Development; Sanggar Sasono Budoyo